Fatal influenza A (H3N2) and campylobacter jejuni coinfection - Kahar-Bador, M.; Nathan, A.M.; Soo, M.H.; Mohd, N.S.; AbuBakar, Sazaly; Lum, L.C.S.; Syed, HS.; Sam, I.C. (2009)
The rapid diagnosis and subtyping of influenza is particularly important in areas where avian influenza (H5N1) is present. The ability to recognise both typical and atypical presentations of influenza is also critical in such settings. A six-month-old male child who visited a H5N1-affected area subsequently died from a severe febrile diarrhoeal illness with minimal respiratory symptoms, and was initially diagnosed with influenza A of an unknown subtype. The final microbiological results showed a highly unusual combination of influenza A (H3N2) and Campylobacter jejuni infection.